An archaeobotanical investigation into the Chalcolithic economy and social organisation of central Anatolia - Stroud, E (2016)
Limited knowledge about the 3000-year period between the Neolithic and the Bronze Age in central Anatolia, Turkey, prevents any understanding of change or continuity in crop production, consumption and crop husbandry techniques. This research aims to address this bias through the examination of archaeobotanical remains from the four central Anatolian Chalcolithic sites of Çatalhöyük West, Çamlıbel Tarlası, Canhasan I and Kuruçay and the consequent investigation of their crop economies. This work draws on multiple methods and techniques to understand the plant-related activities that occurred at the sites. The four chosen sites bookend the Chalcolithic period (c. 6000-3000 cal BC) and provide the opportunity for exploring the interrelationship between crop choice, crop husbandry, settlement size, surrounding environment and social organisation. Differences in crop species such as hulled barley, glume wheats and pulses, particularly lentil and bitter vetch occur at all four sites with species choice community specific. Multiple methods are used to disentangle the depositional processes, such as dung burning, that formed the assemblages, providing an indication of the origin of the archaeobotanical material and allowing inferences about the nature of weed seeds found. Crop processing activities are evident at all sites, with the dehusking of glume wheat contributing significantly to the archaeobotanical assemblage. The analysis of stable carbon and nitrogen isotopes of crops coupled with the functional ecology of arable weeds, indicate that crop husbandry techniques/regimes were site specific and were influenced by site size/population as well as environmental conditions. The identification of the crops grown and the methods used to cultivate and process them have implications for understanding the social context of such activities, and the broader socio-economic background of a period preceding the great changes in social structure seen in the Bronze Age.